Concrete for underground structures - Patel, Rajender (SCITUS Academics LLC, 2016)
Concrete is an essential tool of the underground industry and one that has a significant impact on both the durability and capital cost of a constructed project. Concrete is used in almost every project as tunnel support, backfill, or internal structure. As such, all of the parties to a projectowners, designers, and contractorshave an interest in ensuring that concrete is designed and placed in the most cost-efficient way that ensures an appropriate level of quality in the end product. Concrete is a widely used construction material for bridges, buildings and platforms as well as for underground structures such as tunnels or reinforced concrete pipelines. In general, reinforced concrete is a very durable material capable of withstanding a large range of severe environments including marine, industrial and alpine conditions.